Reflections on the silence of God : a discussion with Marjo Korpel and Johannes de Moor - Becking, Bob.; Moor, Johannes C. de (Johannes Cornelis), 1935-; Korpel, Marjo C. A. (Marjo Christina Annette), 1958- (Leiden ; Boston : Brill, 2013)
Should divine silence be seen as a subtle way of Gods interference with human affairs? Or is to be seen as a sign of his absence? Korpel and de Moor produced a provocative monograph on this topic. This volume contains a set of reactions to their position.
Ex oriente silentium : in introduction to this volume / Bob Becking -- Temple vessels speaking for a silent god : notes on divine presence in the books of Ezra and Nehemiah / Bob Becking -- Divine silence or divine absence? : converging metaphors in family religion in ancient Israel and the Levant / Joel Burnett -- Let sleeping gods lie? : Meindert Dijkstra -- "Der schweigende Gott" : Gedanken zu einem beachtenswerten Buch und einem bedeutenden Thema / Walter Dietrich -- "It shall be night to you, without vision" : the theme of divine disfavour in the Biblical prophetic books / Matthijs de Jong -- How comprehensible can divine silence be? : reflections on the Biblical evidence / Paul Sanders -- Deafening silence? : on hearing God in the midst of suffering / Marcel Sarot -- Speaking from the gaps : the eloquent silence of God in Esther / Anne-Mareike Wetter -- Reaction to the contributions of our reviewers / Marjo Korpel and Johannes de Moor.
Nine contributions in English and 1 in German.
Includes bibliographical references and index.
Print version record.
Keywords: Korpel, Marjo C. A. -- 1958-; Moor, Johannes C. de -- 1935-; God; Hidden God; Belief and doubt; Belief and doubt; God; Hidden God; Korpel, Marjo C.A. (Marjo Christina Annette), 1958- Silent god; Moor, Johannes C. de (Johannes Cornelis), 1935-; RELIGION -- General; Electronic books; Electronic books